Model-based approach for design and performance evaluation of works controlling stony debris flows with an application to a case study at Rovina di Cancia (Venetian Dolomites, Northeast Italy) - Bernard, Martino; Boreggio, Mauro; Degetto, Massimo; Gregoretti, Carlo (The Science of the total environment, 2019)
This paper proposes a methodology for the design and performance evaluation of debris-flow control works based on modeling the phenomenon and its interaction with the works. The reliability of such an approach depends on the trustworthy reproduction of both the phenomenon and its interaction with the structures: the former is provided by simulating all the physical processes concerning the phenomenon (runoff generation, initiation and propagation of a solid-liquid mixture) by models tested against field measurements; the latter by upgrading the propagation model for considering the non-erosive surfaces of the works overflowed or hit by debris flows and computing the forces exerted on them. This methodology is applied to a case study on the Rovina di Cancia channel (northeast Italy), frequently affected by stony debris flows. Longitudinal and transversal works are planned in a reach of the channel subject to high erosion because of its high slope and the supply of water discharge by the Bus de Diau Creek tributary. The works consist of a sectional dam at the end of the reach and in moving there the mouth of the Bus de Diau Creek. Both of them contribute to decrease bed erosion along the reach and to reduce the peak discharge and the transported sediment volume. The proposed methodology is used in the design phase to explore different geometries of the dam opening and choose its transversal position through the analysis of flow (velocity and free surface), whereas, in the evaluation phase, to estimate the reduction in the bed erosion, peak discharge and transported sediment volume provided by the works (i.e. the performance evaluation). Finally, the plot of the forces acting on the dam breakers and bottom over time allows their static dimensioning. [Display omitted] •A model-based procedure for design works mitigating stony debris ow is proposed.•Debris-flow occurrence processes, runoff, triggering and routing are cascade modeled.•The routing model is upgraded for considering non-erosive surfaces.•Simulation results help in the hydraulic design and evaluating the mitigative effects.•The procedure is applied for the design and evaluation of works in a debris-flow channel.